Evaluasi potensi Mata Air Terenapu untuk suplai kebutuhan air bersih penduduk Desa Rendu Butowe Kecamatan Aesesa Selatan Kabupaten Nagekeo - Christian Agustino Boro; Didik Taryana; Ferryati Masitoh (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2022)
Rendu Butowe Village is experiencing a clean water crisis. Residents of Rendu Butowe Village use rainwater and rivers to meet their clean water needs. However, in terms of quantity and quality, these water sources have not been able to meet the needs of the population. Rendu Butowe village has the potential of the Terenapu spring which has not been utilized optimally and has only been used by some residents. The purpose of this study is to determine the potential of the Terenapu spring in terms of quantity and quality of water, to determine the population's clean water needs, and to evaluate the potential of the springs for the needs of the population. The survey method used in the research includes measurement of discharge, analysis of water quality, and interviews of residents' water needs. The results obtained are: the discharge of the Terenapu spring is 1,098,357 liters/day. Parameters of iron, E.Coli and, Total Coliform exceed the requirements for clean water, especially drinking water. The need for clean water for the residents of Rendu Butowe Village is 77,912 liters/day. The discharge of the Terenapu spring can supply the water needs of the residents of Rendu Butowe Village for the next 10 years and the excess discharge can still be optimized for the needs of the residents of Rendu Butowe Village and its surroundings. Desa Rendu Butowe mengalami masalah krisis air bersih. Selama ini, penduduk Desa Rendu Butowe menggunakan air hujan dan sungai dalam memenuhi kebutuhan air bersih. Akan tetapi secara kuantitas dan kualitas sumber air tersebut belum mampu memenuhi kebutuhan penduduk. Desa Rendu Butowe memiliki potensi mata air Terenapu yang belum dilakukan pemanfaatan secara optimal dan baru digunakan oleh beberapa penduduk. Tujuan penelitian ini yaitu mengetahui potensi mata air Terenapu ditinjau dari aspek kuantitas dan kualitas air, mengetahui kebutuhan air bersih penduduk, dan mengevaluasi potensi mata air terhadap kebutuhan penduduk. Metode survei digunakan dalam penelitian, meliputi: pengukuran debit, analisis kualitas air, dan wawancara kebutuhan air penduduk. Hasil yang diperoleh yaitu: debit mata air Terenapu yaitu 1.098.357 liter/hari. Parameter besi, E.Coli dan Total Coliform melebih syarat peruntukan sebagai air bersih khususnya air minum. Kebutuhan air bersih penduduk Desa Rendu Butowe yaitu 77.912 liter/hari. Debit mata air Terenapu mampu menyuplai kebutuhan air penduduk Desa Rendu Butowe hingga 10 tahun kedepan dan kelebihan debit masih dapat di optimalisasikan untuk kebutuhan penduduk Desa Rendu Butowe dan sekitarnya.